Predictive value of red blood cell distribution width for coronary artery lesions in patients with Kawasaki disease. (5th October 2015) - Xu, Haiyan; Fu, Songling; Wang, Wei; Zhang, Qing; Hu, Jian; Gao, Lichao; Zhu, Weihua; Gong, Fangqi
Abstract: Recent studies have shown that elevated red blood cell distribution width is associated with poor outcome in cardiovascular diseases. In order to assess the predictive value of red blood cell distribution width, before treatment with intravenous immunoglobulins, for coronary artery lesions in patient with Kawasaki disease, we compared 83 patients with coronary artery lesions and 339 patients without coronary artery lesions before treatment with intravenous immunoglobulin. Clinical, echocardiographic, and biochemical values were evaluated along with red blood cell distribution width. A total of 422 consecutive patients with Kawasaki disease were enrolled into our study. According to receiver operating characteristic curve analysis, the optimal red blood cell distribution width cut-off value for predicting coronary artery lesions was 14.55% (area under the curve was 0.721; p=0.000); eighty-three patients (19.7%) had coronary artery lesions, and 70% of the patients with coronary artery lesions had red blood cell distribution width level >14.55%. Logistic regression analysis revealed that fever duration >14 days (odds ratio was 3.42, 95% confidence interval was 1.27–9.22; p=0.015), intravenous immunoglobulin resistance (odds ratio was 2.33, 95% confidence interval was 1.02–5.29; p=0.04), and red blood cell distribution width >14.55% (odds ratio was 3.49, 95% confidence interval was 2.01–6.05; p=0.000) were independent predictors of coronary artery lesions in patients with Kawasaki disease. In Conclusion, red blood cell distribution width may be helpful for predicting coronary artery lesions in patients with Kawasaki disease.